2020
DOI: 10.1029/2019jb018310
|View full text |Cite
|
Sign up to set email alerts
|

Shear Velocity and Radial Anisotropy beneath Southwestern Canada: Evidence for Crustal Extension and Thick‐Skinned Tectonics

Abstract: Deformation‐associated craton assembly and Cordilleran orogenesis played major roles during the crustal formation beneath the western margin of North America. To improve the understanding of the deformation history in this region, we investigate the crustal shear velocity and anisotropy by analyzing fundamental mode Rayleigh and Love waves from ambient seismic noise. Continuous recordings from 118 regional broadband stations reveal lateral variations in both velocity and anisotropy with strong spatial affiniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 138 publications
1
5
0
Order By: Relevance
“…Whereas, the negative radial anisotropy is commonly explained by the steeply dipping to the sub-vertical foliation plane of crustal anisotropic materials (Erdman et al, 2013). Continuous lateral crustal shortening under compressional stress could lead to the change in orientation of the foliation plane from sub-horizontal to steeply dipping, which may further cause strong folding and thrusting activities, similar to those widely reported in different orogenic belts (e.g., Chen et al, 2009;J. Wang, Gu, & Chen, 2020;W.…”
Section: Discussionsupporting
confidence: 70%
“…Whereas, the negative radial anisotropy is commonly explained by the steeply dipping to the sub-vertical foliation plane of crustal anisotropic materials (Erdman et al, 2013). Continuous lateral crustal shortening under compressional stress could lead to the change in orientation of the foliation plane from sub-horizontal to steeply dipping, which may further cause strong folding and thrusting activities, similar to those widely reported in different orogenic belts (e.g., Chen et al, 2009;J. Wang, Gu, & Chen, 2020;W.…”
Section: Discussionsupporting
confidence: 70%
“…If there is significant radial anisotropy, the isotropic shear wave velocity will be underestimated (Garber et al., 2018). To date, there have been no detailed studies of the anisotropic V S values in our study area, although anisotropy in the shallow craton has been observed (e.g., Bao et al., 2016; Currie et al., 2004; Wang et al., 2020). The global anisotropy model SUMUCB_WM1 (French & Romanowicz, 2014) shows radial anisotropy in our study area, with horizontal shear wave velocities (V SH ) higher than V SV (Figure 9c).…”
Section: Discussionmentioning
confidence: 83%
“…Rayleigh waves recorded in land seismic surveys, are usually taken as noise and removed in reflection seismic processing. However, these strong coherent arrivals provide high-quality signals for S-wave velocity estimation in the upper tens of meters to tens of kilometers of the Earth (Xia et al, 1999;Shapiro et al, 2005;Gu et al, 2005;Lin et al, 2008;Tape et al, 2010;Strobbia et al, 2011;Nakata et al, 2011;Saygin & Kennett, 2012;Fang et al, 2015;Smith et al, 2019;J. Wang et al, 2020;Tromp, 2020).…”
Section: Introductionmentioning
confidence: 99%